CAR-T Therapy for Pediatric High-Grade Gliomas: Peculiarities, Current Investigations and Future Strategies - Antonucci, Laura; Canciani, Gabriele; Mastronuzzi, Angela; Carai, Andrea; Del Baldo, Giada; Del Bufalo, Francesca (Frontiers in Immunology, 2022)
High-Grade Gliomas (HGG) are among the deadliest malignant tumors of central nervous system in pediatrics. Despite aggressive multimodal treatment - including surgical resection, radiotherapy and chemotherapy - long-term prognosis of patients remains dismal with a 5-year survival rate less than 20%. Increased understanding of genetic and epigenetic features of pediatric HGGs (pHGGs) revealed important differences with adult gliomas which need to be considered in order to identify innovative and more effective therapeutic approaches. Immunotherapy is based on different techniques aimed to redirect the patient own immune system to fight specifically cancer cells. In particular, T-lymphocytes can be genetically modified to express chimeric proteins, known as chimeric antigen receptors (CARs), targeting selected tumor-associated antigens (TAA). Disialoganglioside GD2 (GD-2) and B7-H3 are highly expressed on pHGGs and have been evaluated as possible targets in pediatric clinical trials, in addition to the antigens common to adult glioblastoma – such as interleukin-13 receptor alpha 2 (IL-13α2), human epidermal growth factor receptor 2 (HER-2) and erythropoietin-producing human hepatocellular carcinoma A2 receptor (EphA2). CAR-T therapy has shown promise in preclinical model of pHGGs but failed to achieve the same success obtained for hematological malignancies. Several limitations, including the immunosuppressive tumor microenvironment (TME), the heterogeneity in target antigen expression and the difficulty of accessing the tumor site, impair the efficacy of T-cells. pHGGs display an immunologically cold TME with poor T-cell infiltration and scarce immune surveillance. The secretion of immunosuppressive cytokines (TGF-β, IL-10) and the presence of immune-suppressive cells – like tumor-associated macrophages/microglia (TAMs) and myeloid-derived suppressor cells (MDSCs) - limit the effectiveness of immune system to eradicate tumor cells. Innovative immunotherapeutic strategies are necessary to overcome these hurdles and improve ability of T-cells to eradicate tumor. In this review we describe the distinguishing features of HGGs of the pediatric population and of their TME, with a focus on the most promising CAR-T therapies overcoming these hurdles.